Faktor-Faktor Peserta Jaminan Kesehatan Nasional (JKN) Penerima Bantuan Iuran (PBI) yang behubungan dengan Pemanfaatan Pelayanan Kesehatan di Wilayah Kerja Puskesmas Mandala Mekar Kota Bandung - Gugum Pamungkas; Neli Naelul Inayah (stikes dharma husada bandung, 2020)
Health insurance is a guarantee in the form of health protection so that participants get the benefits of health care and protection in meeting basic health needs. National Health Insurance membership consists of Beneficiary Contribution (PBI) and not PBI. Mandala Mekar Health Center is the health center with the lowest number of visits, 866 (30,6%) out of 2,827 (69,4%) National Health Insurance participants, with PBI participants totaling 1867 (66%) participants. The purpose of this study was to determine the factors of PBI National Health Insurance Participants (JKN) related to the utilization of health services in the working area of ​​the Mandala Mekar Community Health Center in Bandung. The research method was quantitative, cross sectional design with a population of 1867 (66%) PBI participants. Sampling with Accidental sampling technique as many as 72 people. Data analysis using Chi Square Test. The results of the study, which utilized the health services of 28 people (38,9 %) and who did not utilize 44 people (61,1%). There is a relationship between age, utilization of health services with (p = 0.007) and attitude (p = 0.011). There is no relationship of belief, location of facilities, and needs with the utilization of health services.